(untitled) (The International Journal for Scientific Research, 2026)
This study aims to construct a causal model explaining the relationships between self-efficacy and grit as independent variables, coping strategies as a mediating factor, and academic resilience as a dependent variable among high school female students in Jeddah. The study employed a descriptive correlational research design, utilizing Structural Equation Modeling (SEM) to examine the nature of both direct and indirect relationships between the variables. The study sample consisted of 506 female students, randomly selected from a number of public and private high schools. To achieve the study objectives, the researcher administered four standardized psychological scales, namely the General Self-Efficacy Scale (GSE), the GRIT Scale, the Academic Resilience Scale, and the adaptive and maladaptive forms of the Coping Strategies Scale (CSS). Data were analyzed using SPSS Statistics 29.0, Mplus 7.0, and the Lavaan package in Jamovi 2.6 to test the validity of the hypothesized model and the statistical adequacy of the path estimates. The results showed that the students exhibited a high level of self-efficacy and possessed strong passion and motivation toward goals, with a moderate level of long-term perseverance. A generally high level of academic resilience was also observed, with the Grit dimension standing out as the strongest predictor of resilience among all dimensions. Analyses further revealed statistically significant positive direct effects of both self-efficacy and grit on coping strategies, as well as a positive direct effect of coping strategies on academic resilience. However, no significant direct effect of self-efficacy or grit on academic resilience was observed; instead, an indirect effect was mediated through adaptive coping strategies, highlighting the mediating role of these strategies in the proposed causal model. These results underscore the importance of developing school-based guidance programs informed by the study’s causal model, aimed at improving self-efficacy and grit, and training students in positive coping strategies to enhance academic resilience.